Enhancing the saccharolytic phase of sugar beet pulp via hemicellulase synergy - Dredge, Roselyn Ann (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2010)
The sugar beet (Beta vulgaris) plant has in recent years been added to the Biofuel Industrial Strategy (Department of Minerals and Energy, 2007) by the South African government as a crop grown for the production of bio-ethanol. Sugar beet is commonly grown in Europe for the production of sucrose and has recently been cultivated in Cradock and the surrounding areas (Engineering News, 2008). The biofuel industry usually ferments the sucrose with Saccharomyces cerevisiae to yield bio-ethanol. However, researchers are presented with a critical role to increase current yields as there are concerns over the process costs from industrial biotechnologists. The beet factories produce a pulp by-product removed of all sucrose. The hemicellulose-rich pulp can be degraded by microbial enzymes to simple sugars that can be subsequently fermented to bio-ethanol. Thus, the pulp represents a potential source for second generation biofuel. The process of utilising microbial hemicellulases requires an initial chemical pre-treatment step to delignify the sugar beet pulp (SBP). An alkaline pre-treatment with 'slake lime' (calcium hydroxide) was investigated using a 23 factorial design and the factors examined were: lime load; temperature and time. The analysed results showed the highest release of reducing sugars at the pre-treatment conditions of: 0.4 g lime / g SBP; 40Â°C and 36 hours. A partial characterisation of the Clostridium cellulovorans hemicellulases was carried out to verify the optimal activity conditions stated in literature. The highest release of reducing sugars was measured at pH 6.5 "“ 7.0 and at 45Â°C for arabinofuranosidase A (ArfA); at pH 5.5 and 40Â°C for mannanase A (ManA) and pH 5.0 "“ 6.0 and 45Â°C for xylanase A (XynA). Temperature studies showed that a complete loss of enzymatic activity occurred after 11 hours for ManA; and 84-96 hours for ArfA. XynA was still active after 120 hours. The optimised lime pre-treated SBP was subsequently degraded using various combinations and percentages of C. cellulovorans ArfA, ManA and XynA to determine the maximal release of reducing sugars. Synergistically, the highest synergy was observed at 75% ArfA and 25% ManA, with a specific activity of 2.9 Î¼mol/min/g protein. However, the highest release of sugars was observed at 4.2 Î¼mol/min/g protein at 100% ArfA. This study has initiated the research within South Africa on SBP and its degradation by C. cellulovorans. Preliminary studies show that SBP has the potential to be utilised as a second generation biofuel source.
Keywords: Sugar plantations; Sugar plantations -- South Africa; Sugar beet industry -- South Africa; Saccharomyces cerevisiae -- Biotechnology; Biomass energy industries -- South Africa